Increase in Dengue cases in São Paulo from 2023 to 2025: An epidemiological analysis (Research, Society and Development, 2025)
The objective of this article is to present an analysis of the increase in dengue cases in the state of São Paulo between 2023 and 2025, investigating epidemiological trends and the factors that contributed to the growth in disease incidence.Dengue, transmitted by the Aedes aegypti mosquito, continues to pose a major public health challenge in Brazil, exacerbated by urbanization, poor sanitation, and rising temperatures. The research indicates a significant rise in cases, especially in areas with higher population density, such as the capital and Greater São Paulo. The introduction of the dengue vaccine into the Unified Health System (SUS) in 2023 marked an important step forward, but vector control remains essential. The article also discusses preventive actions, including the management of mosquito breeding sites and community mobilization. It concludes that the combination of preventive measures, vaccination, and active public engagement is crucial for containing the disease and improving public health in the country.